Strategic Transformation of Healthcare Personnel Training Planning at Poltekkes Bandung - Heriyanto, Yonan; Adiwisastra, Josy; Broto, Mani Festati; Muhtar, Entang Adhy (Jurnal Manajemen Pelayanan Publik, 2026)
This research highlights the ineffectiveness of the health human resources (HR) competency development policy at Poltekkes Bandung, which is characterized by a low rate of transfer of learning from training outcomes to the workplace, the absence of a monitoring system leading to skill decay, an imbalance between hard skills and soft skills, and top-down planning that triggers an implementation gap. Using qualitative methods and NVivo 12 analysis on 12 informants, this research reconstructs a demand-driven planning model through an Interprofessional Collaboration (IPC) approach and digitalization. The results formulate an integrated seven-step model, including: synchronizing the curriculum with medical infrastructure, optimizing the Triple Helix partnership, implementing an inclusive IPC curriculum to break down the sectoral (silo-based) work culture, and utilizing the "Plataran Sehat" platform for digital monitoring. This transformation is an absolute prerequisite to eliminate bureaucratic inefficiencies and technical failures in the field. By integrating the monitoring system and cross-professional collaboration, Poltekkes Bandung can transform into a catalyst for responsive and accountable HR development to support the achievement of the Golden Indonesia 2045 vision.